Integrating seaweed ethnoscience with STEM-PjBL in renewable energy learning: Could this approach develop creativity and entrepreneurial skills? - Putri, Cindi Ratna; Abdurrahman, Abdurrahman; Herlina, Kartini (Universitas Islam Negeri Raden Intan Lampung, 2025)
The urgency of this research stems from the lack of application of the Ethnoscience-STEM-PjBL (Science, Technology, Engineering, and Mathematics - Project-Based Learning) approach in renewable energy learning, the limited availability of teaching materials based on local wisdom, and the lack of supporting learning resources. This study aims to describe the perceptions of teachers and students toward renewable energy learning using this approach to foster creativity and entrepreneurial skills. This research employed the sequential embedded design method, involving 30 physics teachers from Lampung Province. Data were gathered through questionnaires and analyzed descriptively. The findings reveal that while teachers generally hold positive perceptions of the Ethnoscience-STEM-PjBL approach, most have yet to implement it in their classrooms. The implication of this study highlights the urgent need to develop culturally relevant teaching materials and provide targeted teacher training. Such efforts are essential to facilitate the effective integration of the Ethnoscience-STEM-PjBL model in renewable energy education, thereby enhancing both student engagement and the relevance of science learning in local contexts.